Benefits of Cover Crops for Soil Health - Yoana C. Newman; David L. Wright; Cheryl Mackowiak; J.M.S. Scholberg; C. M. Cherr (EDIS)
SS-AGR-272, a 4-page fact sheet by Y.C. Newman, D.W. Wright, C. Mackowiak, J.M.S. Scholberg and C.M. Cherr, discusses the benefits of cover crops in agricultural production, the benefits of soil organic matter; how to match cover crop nutrient release with future crop demand; timing and depth of residue incorporation; and erosion, pest and weed control. Includes references. Published by the UF Department of Agronomy, November 2007.